Neuromuscular recovery from botulism involves multiple forms of compensatory plasticity - Machamer, James B.; Vazquez-Cintron, Edwin J.; Stenslik, Mallory J.; Pagarigan, Kathleen T.; Bradford, Aaron B.; Ondeck, Celinia A.; McNutt, Patrick M. (Frontiers in Cellular Neuroscience, 2023)
Botulinum neurotoxin (BoNT) causes neuroparalytic disease and death by blocking neuromuscular transmission. There are no specific therapies for clinical botulism and the only treatment option is supportive care until neuromuscular function spontaneously recovers, which can take weeks or months after exposure. The highly specialized neuromuscular junction (NMJ) between phrenic motor neurons and diaphragm muscle fibers is the main clinical target of BoNT. Due to the difficulty in eliciting respiratory paralysis without a high mortality rate, few studies have characterized the neurophysiological mechanisms involved in diaphragm recovery from intoxication. Here, we develop a mouse model of botulism that involves partial paralysis of respiratory muscles with low mortality rates, allowing for longitudinal analysis of recovery. Mice challenged by systemic administration of 0.7 LD50 BoNT/A developed physiological signs of botulism, such as respiratory depression and reduced voluntary running activity, that persisted for an average of 8-12 d. Studies in isolated hemidiaphragm preparations from intoxicated mice revealed profound reductions in nerve-elicited, tetanic and twitch muscle contraction strengths that recovered to baseline 21 d after intoxication. Despite apparent functional recovery, neurophysiological parameters remained depressed for 28 d, including end plate potential (EPP) amplitude, EPP success rate, quantal content (QC), and miniature EPP (mEPP) frequency. However, QC recovered more quickly than mEPP frequency, which could explain the discrepancy between muscle function studies and neurophysiological recordings. Hypothesizing that differential modulation of voltage-gated calcium channels (VGCC) contributed to the uncoupling of QC from mEPP frequency, pharmacological inhibition studies were used to study the contributions of different VGCCs to neurophysiological function. We found that N-type VGCC and P/Q-type VGCC partially restored QC but not mEPP frequency during recovery from paralysis, potentially explaining the accelerated recovery of evoked release versus spontaneous release. We identified additional changes that presumably compensate for reduced acetylcholine release during recovery, including increased depolarization of muscle fiber resting membrane potential and increased quantal size. In addition to identifying multiple forms of compensatory plasticity that occur in response to reduced NMJ function, it is expected that insights into the molecular mechanisms involved in recovery from neuromuscular paralysis will support new host-targeted treatments for multiple neuromuscular diseases.